The western transmission of traditional Chinese medicine: an investigation of the cultural elements of traditional Chinese medicine in biomedical systems of cross-Asia countries - Kadier, Aibibula; Ablimit, Mihray; Tursun, Hebibulla; Ablat, Nuramatjan (Frontiers in Pharmacology, 2025)
The globalization of Traditional Chinese Medicine (TCM) has facilitated its integration into healthcare systems beyond China, particularly in cross-Asia countries such as Japan, Korea, and Vietnam, while influencing biomedical practices worldwide. This review explores the cultural, historical, and scientific dimensions of TCM’s transmission, focusing on how its foundational theories (e.g., Yin-Yang, Qi-Blood, and Five Elements) and practices (e.g., acupuncture, herbal formulations) have been adapted and validated in diverse sociocultural contexts. We analysed primary literature from data collected by PubMed, Google Scholar, CNKI, Web of Science, Bing, Baidu, and Scopus (1990–2024). Our review critically evaluates the scientific evidence supporting TCM-derived bioactive metabolites like artemisinin from Artemisia annua L. [Asteraceae] and berberine from Coptis chinensis Franch. [Ranunculaceae], examining their concentrations, bioavailability, and clinical applications. Challenges such as standardization, intellectual property disputes, and cultural reinterpretation are critically evaluated. This paper systematically argues that TCM’s cross-cultural transmission reflects a dynamic interplay between tradition and modern biomedicine, offering a model for integrating traditional knowledge into global healthcare while highlighting the limitations of current research and areas requiring further investigation.